2005
DOI: 10.1103/physrevb.72.220402
|View full text |Cite
|
Sign up to set email alerts
|

Influence of domain wall interactions on nanosecond switching in magnetic tunnel junctions

Abstract: We have obtained microscopic evidence of the influence of domain wall stray fields on the nanosecond magnetization switching in magnetic trilayer systems. The nucleation barrier initiating the magnetic switching of the soft magnetic Fe 20 Ni 80 layer in magnetic tunnel junctionlike FeNi/ Al 2 O 3 / Co trilayers is considerably lowered by stray fields generated by domain walls present in the hard magnetic Co layer. This internal bias field can significantly increase the local switching speed of the soft layer. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 22 publications
0
26
0
Order By: Relevance
“…Magnetic imaging of layered systems can provide crucial information that may not be accessible otherwise. For example, magnetic stray fields generated by domain walls in the hard layer of a tunnel junction can significantly reduce the energy barrier to nucleate domains in the soft layer during magnetization reversal [124]. In micron-sized, ellipseshaped spin valve structures, the magnetic stray field of the hard layer is also known to induce 360…”
Section: Magnetic Coupling In Layered Structuresmentioning
confidence: 99%
“…Magnetic imaging of layered systems can provide crucial information that may not be accessible otherwise. For example, magnetic stray fields generated by domain walls in the hard layer of a tunnel junction can significantly reduce the energy barrier to nucleate domains in the soft layer during magnetization reversal [124]. In micron-sized, ellipseshaped spin valve structures, the magnetic stray field of the hard layer is also known to induce 360…”
Section: Magnetic Coupling In Layered Structuresmentioning
confidence: 99%
“…In this section we will show that also inhomogeneities in the magnetization of the hard layer, like the presence of magnetic domain walls, can influence the magnetization reversal of the soft layer. In a previous paper 12 , we have shown that a domain wall in the Co layer of sample II locally decreased the barrier for domain nucleation in the FeNi layer. We have performed time-resolved XMCD-PEEM measurements also on the other samples, in order to confirm that the preferential nucleation induced by domain wall stray fields is a general property of this type of trilayers.…”
Section: Influence Of Domain Wallsmentioning
confidence: 99%
“…This effect can be understood by taking into account the domain wall stray field. In our previous paper, 12 we have discussed the effect of this stray field. In particular, micromagnetic simulations have shown that the Co domain wall stray field is sufficient to create a region where the FeNi magnetization is tilted away from the easy axis, creating a so-called quasi-wall.…”
Section: Influence Of Domain Wallsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notice however, that even in this weak coupling limit dipolar fields may be locally much more intense than HN when domain walls occur, like during magnetization reversal [120]. This may lead to progressive demagnetization of the hard layer of spin valves [121] or nucleation of reversed domains in the vicinity of domain walls [122]. In the strong coupling limit HN is larger than both coercive fields, resulting in rigidly coupled layers.…”
Section: Coupled Layersmentioning
confidence: 98%